Numerical Modelling of Complex Flows With Sprays Including Electrostatic Effects - Pendar, Mohammad-Reza (2021)
During the past two decades, the Electrostatic Rotary Bell Sprayers (ERBSs), because of their superior transfer efficiency (TE) and coating performance, lower environmental destructive effects and cost decrement, attract the attention of many researchers in the coating industry. In this thesis, we developed a 3D comprehensive Eulerian-Lagrangian algorithm in order to investigate the fundamental behaviors of the flow in an electrostatic rotary bell sprayer (ERBS) during the formation of the droplets and depositing on a target. This efficient extended algorithm contains a model for airflow field, spray dynamics, electric field, droplet charge, droplet trajectory tracking and wall film dynamics. The fluid-dynamics is simulated by solving the unsteady 3D compressible Navier-Stokes equations. Unsteady flow is computed by using a Large eddy simulation (LES) turbulence approach, while the motion of the particles is simulated by tracking the droplet size distribution approach. The algorithm is implemented under the framework of the OpenFOAM package. Creating an initial condition of the particle approach has been proposed that is matched with practical applications. The present work contains a systematic analysis of the recirculation zone length, the toroidal vortex, the overspray phenomena and the flowfield characteristics like mean velocity, pressure, turbulent kinetic energy and velocity fluctuation. Also, the presented results describe exact values for the size, distribution, velocity, and trajectory of the particles in the ERBS. These results are important for coating industries to optimize their working conditions. The effect of operational parameters like bell rotational speed, shaping air and paint flow rate, electrical charge values and droplet size distributions are considered precisely. The results indicate as a main operating parameter the air-paint flow rate with voltage level deeply affecting the spray shape. The effect of the bell rotational speed in comparison with other parameters is dominant. The paint spray distribution obtained in the present work is validated against coating experimental results with suitable accuracy. Investigation of the various primary and secondary breakup models is one of the main goals of this work to predict the droplet size more precisely. The Reitz-KHRT, Reitz- Diwakar, Pilch-Erdman and the newly modified TAB model are examined in order to predict the secondary breakup process in the ERBS. Here, the implemented wall film function is able to predict the transport in the boundary layer over the target. This study also presents a performance evaluation of the ERBS with a particular focus on droplet charge, electric field, ambient conditions with the implementation of a highvoltage control-ring field pattern effect into the fully turbulent airflow and by including the atomized droplets discrete phase. The results indicate that the new proposal of using a control-ring operation improves the performance and transfer efficiency (TE) of the ERBS, and it also helps to harmonize the direction of the charged paint droplets. Furthermore, a novel electrostatic spraying system by using high-voltage retractable blades or high-voltage adjustable control ring is also presented in the current study as a recent patent. Also, some other useful applications of the implemented code are presented. First, the modified spraying part of the code is used, leading to a deeper understanding of the saliva-disease-carrier droplets transmission mechanisms as an atomized droplets during sneezing, coughing, or even exhaling. This is particularly important to ensure safety conditions in the work environment. Second, the implemend electrical field that was added to the code is considered without injecting droplets to accurately simulate the plasma flow by using a multi dielectric-barrier-discharge (DBD) plasma actuator over a 3D-airfoil difference. This shows the versatility of the developed model.